I stormens öga räcker status quo föga - Lennartsson, Andreas; Reuterdahl Svedberg, Elsa (2021)
A company’s external environment consists of external, ever-changning forces that force it to adapt (Mintzberg, 2005). The company’s value network is part of this external environment; the value network is the link between the company and its external environment (Allee, 2000). Sometimes, the external forces of the company's environment accumulate into an extreme, unforeseen force of change – in this thesis, such extreme external change mechanisms are understood as crises. As the external environment changes, entrepreneurial opportunities materialise, which the company may act upon; this is more evident during extreme external crises. In addition, an important asset in the company's corporate brand plays an important role for its ability to discover and act upon entrepreneurial opportunities (Argentini and Druckenmiller, 2014). The purpose of this qualitative study is to investigate how companies in the restaurant industry initiate various change processes due to external changes caused by crisis, and how these change processes relate to corporate branding. The research strategy employs an inductive approach. The empirical material has been collected through a case study where, in which semi-structured interviews were conducted. The study indicates that entrepreneurial opportunities occurs as a result of changes in the external environment in the company's value network. Those opportunities identified by the company are short-term layoffs, a take-away service, a reduced business system and a turnover-based business model. The company have acted on some of the entrepreneurial opportunities and remained passive with regards to some. In conclusion, the entrepreneurial opportunities on which the company has acted upon have resulted in company change.